2017
DOI: 10.1101/119529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of long-term balancing selection in human genomes

Abstract: Balancing selection maintains advantageous diversity in populations through various mechanisms. While extensively explored from a theoretical perspective, an empirical understanding of its prevalence and targets lags behind our knowledge of positive selection. Here we describe the Non-Central Deviation (NCD), a simple yet powerful statistic to detect long-term balancing selection (LTBS) that quantifies how close frequencies are to expectations under LTBS, and provides the basis for a neutrality test. NCD can b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 108 publications
3
47
0
Order By: Relevance
“…The contribution of balancing selection to standing genetic variation can also be substantial (Bitarello et al 2018;Good et al 2017;Charlesworth 2015). In a particularly striking example, sequencing studies in temperate Drosophila populations have found hundreds of polymorphic loci that undergo seasonal oscillations in allele frequency (Bergland et al 2014;Machado et al 2018).…”
mentioning
confidence: 99%
“…The contribution of balancing selection to standing genetic variation can also be substantial (Bitarello et al 2018;Good et al 2017;Charlesworth 2015). In a particularly striking example, sequencing studies in temperate Drosophila populations have found hundreds of polymorphic loci that undergo seasonal oscillations in allele frequency (Bergland et al 2014;Machado et al 2018).…”
mentioning
confidence: 99%
“…Moreover, our SURFDAWave approach is not restricted to application on adaptive introgression and selective sweep scenarios, and can be implemented for probing genomic variation of other evolutionary processes that leave a spatial or temporal signature in genomic data. Such examples include the identification of genomic targets of balancing selection (e.g., DeGiorgio et al, 2014;Siewert and Voight, 2017;Bitarello et al, 2018;Cheng and DeGiorgio, 2018;Siewert and Voight, 2018;, complex forms of adaptation such as staggered selective sweeps (Assaf et al, 2015) that have yet to be interrogated for in genomic data, and non-adaptive processes such as recombination rate estimation (e.g., Chan et al, 2018;Flagel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An implication is that estimation of F ST is robust to ascertainment for ancestral polymorphisms based on common ancestors older than the chimpanzee-human common ancestor. Empirical evidence suggests that the number of loci under long-term balancing selection in humans is on the order of tens or hundreds, not tens of thousands [31,32] .…”
Section: Discussionmentioning
confidence: 99%